1979
DOI: 10.1021/j100482a020
|View full text |Cite
|
Sign up to set email alerts
|

Studies on spin-trapped radicals in .gamma.-irradiated aqueous solutions of DL-methionine by high performance liquid chromatography and ESR spectroscopy

Abstract: Short-lived radicals produced in -irradiated aqueous solutions of DL-methionine were converted into relatively stable spin adducts by means of spin trapping, and the spin adducts were identified by high performance liquid chromatography and ESR spectroscopy. Four spin adducts were found and their structures identified as follows:CH3SCH2CH2CH(C00-)-N(0•)-^, ' -(0.)-2 2 ( 2)000-, CH3-N(OHBu, tRu-NÍO-HEu.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…The observation of two intermediates in the auto-reduction of bis -Fe(IV) MauG by UV-Vis spectroscopy makes MauG a promising candidate for the characterization or capture of a methionine radical in a protein. Previously characterized methionine radicals were generated photochemically with free amino acids, leaving an open question as to how a protein environment might affect a methionine radical [26, 33]. We sought to characterize or capture any possible radical species formed during the return of bis -Fe(IV) MauG to the resting state.…”
Section: Discussionmentioning
confidence: 99%
“…The observation of two intermediates in the auto-reduction of bis -Fe(IV) MauG by UV-Vis spectroscopy makes MauG a promising candidate for the characterization or capture of a methionine radical in a protein. Previously characterized methionine radicals were generated photochemically with free amino acids, leaving an open question as to how a protein environment might affect a methionine radical [26, 33]. We sought to characterize or capture any possible radical species formed during the return of bis -Fe(IV) MauG to the resting state.…”
Section: Discussionmentioning
confidence: 99%
“…However, if methionine acts as an antioxidant by reacting with reactive oxygen‐ and nitrogen‐derived species [9,10], it should be oxidized by both two‐ and one‐electron mechanisms [11,12]. Indeed, the oxidation of free and peptide‐bound methionine to radical intermediates has been demonstrated before [11–15]. Likewise, methionine oxidation beyond the sulfoxide level may occur, particularly through one‐electron mechanisms because methionine sulfone has rarely been detected under physiological conditions [1].…”
Section: Introductionmentioning
confidence: 99%
“…These results suggested that ionizing radiation elicits epigenetic changes mediated by oxidative stress. It is reasonable to speculate that the initial seeds of methylation are formed by a free radical mechanism because methyl radicals are generated by the γ -irradiation of methionine, an endogenous molecule (31) .…”
Section: Discussionmentioning
confidence: 99%
“…When RNA was reacted with this system, 8-methylguanine, 2-methyladenine, and 8-methyladenine were detected in the acid hydrolysate. Makino (31) reported methyl radical production in a γ -irradiated aqueous solution of dl -methionine, as detected by ESR spectroscopy. Nakao et al (32) reported that both free and peptide-bound MetO are oxidized by hydrogen peroxide/iron(II)-EDTA and peroxynitrite, through a hydroxyl radical intermediate, to produce a methyl radical.…”
Section: Generation Of Methyl Radicals and Their Reactions With Nuclementioning
confidence: 99%